Why TAPBPR? Implications of an additional player in MHC class I peptide presentation. (June 2021) - Hafstrand, Ida; Aflalo, Aure; Boyle, Louise H
Highlights: Characterisation of TAPBPR has reveal new insights into MHC-I peptide editing. Polymorphism in MHC-I alter their susceptibility to TAPBPR-mediated peptide editing. Recent findings suggest TAPBPR functionality beyond classical MHC-I. Abstract : The peptide editor TAPBPR is the newest member of the major histocompatibility complex class I (MHC-I) antigen processing and presentation pathway. Since 2013, studies have explored the functions and mechanisms of action of this tapasin homolog. Here, we review the key insights gained from structural studies of the TAPBPR:MHC-I complex and the involvement of the TAPBPR loop in peptide exchange. However, despite recent advances, the question still remains: why do we need TAPBPR? The recent appreciation that different MHC-I allotypes vary in their ability to interact with TAPBPR, together with a role for TAPBPR in alternative presentation pathways highlights that much remains unknown concerning the biological need for TAPBPR.